2018
DOI: 10.1088/1742-6596/1033/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Researches on Tie Rod Ends Lubricated by Grease with TiO2 and ZrO2 Nanoparticles

Abstract: Abstract. The nanoparticles of some materials can be used successfully to improve tribological properties through decreasing both wear and friction borne out of contact between the contact surfaces of elements in different devices, particularly vehicles. Nanoparticles of TiO2 and ZrO2 were chosen as additives to the lithium grease lubricating the contact surfaces in tie rod ends. The object of study was the steel ball -the component of the tie rod end -mating with the polymer insert and lubricated with the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The preliminary analysis of the nanopowder market, particularly in Poland, has shown that zirconia nanopowders are available on the market and are relatively cheap. The number of available publications on the use of ZrO 2 nanoparticles as an additive to lubricants is not great; nevertheless, the results of preliminary studies carried out by Wozniak et al [61] pointed such nanoparticles as a candidate improving the tribological properties of some lubricants. It has been noted that the problem of agglomeration may also occur during preparation of nanolubricants with zirconia nanoparticles.…”
Section: Factors Affecting the Agglomerationmentioning
confidence: 99%
See 4 more Smart Citations
“…The preliminary analysis of the nanopowder market, particularly in Poland, has shown that zirconia nanopowders are available on the market and are relatively cheap. The number of available publications on the use of ZrO 2 nanoparticles as an additive to lubricants is not great; nevertheless, the results of preliminary studies carried out by Wozniak et al [61] pointed such nanoparticles as a candidate improving the tribological properties of some lubricants. It has been noted that the problem of agglomeration may also occur during preparation of nanolubricants with zirconia nanoparticles.…”
Section: Factors Affecting the Agglomerationmentioning
confidence: 99%
“…Wozniak et al [61] studied lithium grease with the TiO 2 and ZrO 2 nanoparticles lubricating the mating surfaces in tie rod ends. The steel ball-polymer insert contact zone was lubricated with the pure lithium grease or containing 1 wt.% of TiO 2 or ZrO 2 nanoparticles.…”
Section: Nanoparticles As Additive To Lithium Greasementioning
confidence: 99%
See 3 more Smart Citations